Conflict and Collaboration: Providers and Planners Implementing the Workforce Investment Act (WIA) - John L. Hopkins; Catherine A. Hansman; Catherine H. Monaghan (Adult Education Research Conference, 2009)
This qualitative case study investigated the impact of WIA funding on the providers and planners of programs for incumbent workers in one Midwest WIA region, examining the collaboration and power conflicts that are part of planning and implementing this legislation. The study applied Matland’s (1995) ambiguity/conflict framework to WIA implementation.